Knowledge, practices, and epidemiology of bovine fasciolosis in smallholder farming areas of South Africa - Marufu, Munyaradzi Christopher (University of Pretoria, 2023)
Thesis (PhD (Production Animal Studies))--University of Pretoria, 2022.